2001
DOI: 10.1039/b105514n
|View full text |Cite
|
Sign up to set email alerts
|

Ar scattering on Ru (0001): a comparison to the washboard modelPresented at the Stereodynamics 2000 Conference on Dynamics and Stereodynamics of Chemical Reactions, El Escorial, Madrid, December 1–5, 2000.

Abstract: The scattering of Ar atoms on a Ru (0001) surface has been studied by applying supersonic molecular beam techniques. Variation of the incidence energy (E i ) results in a rich variety of angular and energy distributions. At a low energy, clear zero-order diffraction has been identified. At higher energies (5 1 eV), argon scattering of Ru (0001), however, seems to be dominated by a totally different mechanism, which appears to be almost quantitatively reproduced by the washboard model, developed by Tully (J. C.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 9 publications
3
41
0
Order By: Relevance
“…These include Xe-Ni͑111͒, 3 Xe-Pt͑111͒, 4,5 Xe-GaAs͑100͒, 6 Xe-Ag͑100͒, 6 Xe-Ge͑100͒, 6 Ar-Pt͑111͒, 5 Ar-Ag͑111͒, 7 and Ar-Ru͑0001͒. 8 For incident energies greater than about 1 eV, the angular distribution of the scattered flux is concentrated in one peak whose intensity maximum is at the specular or larger angle. In general, this distribution is fairly narrow, at least for the lowest surface temperatures, with a fullwidth half-maximum ͑FWHM͒ of ϳ10°-20°.…”
Section: Introductionmentioning
confidence: 98%
“…These include Xe-Ni͑111͒, 3 Xe-Pt͑111͒, 4,5 Xe-GaAs͑100͒, 6 Xe-Ag͑100͒, 6 Xe-Ge͑100͒, 6 Ar-Pt͑111͒, 5 Ar-Ag͑111͒, 7 and Ar-Ru͑0001͒. 8 For incident energies greater than about 1 eV, the angular distribution of the scattered flux is concentrated in one peak whose intensity maximum is at the specular or larger angle. In general, this distribution is fairly narrow, at least for the lowest surface temperatures, with a fullwidth half-maximum ͑FWHM͒ of ϳ10°-20°.…”
Section: Introductionmentioning
confidence: 98%
“…However, diffraction is usually strong only for thermal energy helium, due to its small mass. Inelastic scattering tends to dominate for heavier probe atoms unless particular experimental conditions, such as low surface temperatures or grazing incidence reflection, are adopted [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. Unexpectedly, early neon atom scattering measurements also revealed diffraction peaks [1,2], even though the ordinary Debye-Waller theory predicted them to be unobservably weak.…”
Section: Introductionmentioning
confidence: 99%
“…First, it must be recalled that (13) is only a classical, or high-temperature, approximation to the quantum expression for B(τ ) given by (12). The latter contains a complex factor exp(iωτ ) in the zero-point term.…”
Section: Scattering From An Einstein Modelmentioning
confidence: 99%
“…Previous studies of rare-gas and diatomic molecular scattering from clean Ru(0001) have revealed a large effective mass. An analysis of the energy-resolved spectra of Ar scattering from Ru(0001) [42,43] as well as scattering of N 2 molecules from similar Ru(0001) [44,45] gave for both projectile particles an effective mass of approximately 2.5 Ru atoms. Based on the analysis of those two systems it was proposed that the Ru(0001) surface would present a large effective mass for the scattering of all the rare gases and even for other projectiles [46].…”
Section: Surface Effective Masses From Ar Scatteringmentioning
confidence: 99%